Postoperative pulmonary embolism, risk factors, and medical thromboprophylaxis: a 2-year retrospective study - Eman Sobh; Maisa A Abdel Wahab; Zeinab R Adawy; Heba M Abdelgalil; Ola I Saleh; Doaa M Zakaria; Randa S Elshahat (Wolters Kluwer Medknow Publications, 2022)
Background and aim The major surgical procedures have a significant risk of venous thromboembolism (VTE), especially pulmonary embolism (PE), leading to poor prognosis and life-threatening conditions. The major surgical procedure has 20-fold risk increase in VTE and the risk is increased by 30% in the absence of optimal prophylaxis. This study aimed to estimate the incidence of PE among surgical patients undergoing preoperative thromboprophylaxis according to Caprini score, these considerations can improve the clinical outcome and allow optimal use of thromboprophylactic strategies against VTE. Patients and methods We performed retrospective analysis of records of patients admitted to surgical wards at our hospital and identified those who developed postoperative PE. We calculated Caprini score to assess the risk for VTE. Results Among patients admitted to surgical wards, we identified 107 cases of postoperative PE. Most of them had major surgeries, most of them were females, and a considerable proportion of those who developed PE did not receive thromboprophylaxis although being at moderate or high risk for VTE according to Caprini score. Few patients had poor outcome. Conclusion Perioperative thromboprophylaxis is crucial to avoid complication with VTE. Caprini score may be a good clinical score to decide which patients to receive perioperative thromboprophylaxis.